Adenomyoepithelioma with Ductal Carcinoma In Situ: A Case Report and Review of the Literature - Sanjay Warrier; Sang Hwang; Martha Ghaly; Alex Matthews (Case Reports in Surgery)
Adenomyoepithelioma (AME) with microglandular adenosis-like growth pattern and superimposed ductal carcinoma in situ (DCIS) was identified in a 55-year-old female after biopsy of an atypical lesion identified through routine breast screening. A literature review reveals that this association has rarely been described.